URGENCY OF PSYCHOLOGICAL FOUNDATION FOR CURRICCULUM DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION IN 21st CENTURY - Mela Mariana (Fakultas Tarbiyah, Universitas Ibrahimy, 2024)
The ability of teachers to design the right curriculum, especially in Islamic religious education, can be a benchmark for achieving educational goals. This study aims to reveal the correlation of psychological foundations in the development of Islamic religious education curriculum and its relevance in 21st-century learning. The type of research used in this study is library research through the stages of content analysis. In this study, two points were produced from the references used. First, the implications of learning psychology in the PAI curriculum. Second, there is a strong relevance between the principles of psychology and the development of the PAI curriculum in 21st-century learning, one of which is gestalt theory and the adoption of the concept of 21st-century education in the Decree of the Ministry of Religious Affairs of the Republic of Indonesia regarding the PAI curriculum and Arabic. Thus, it can be concluded that the relationship between psychology principles and the PAI curriculum is very important. Understanding this aspect of psychology plays a vital role in determining the success of teachers in achieving educational goals in accordance with the demands of the times.